The Cat's Paw - Taylor, Sam; Lundin, Walter; Lloyd, Harold; Merkel, Una; Barbier, George (Harold Lloyd - The 10 Disc Collection, 2008)
Ezekiel Cobb, the only son of missionaries posted to rural China in 1914, returns to Stockport, California, in 1934 to find 'a mother for his children'. He has a letter of introduction to the head of the mission, but the man turns out to be the cat's paw of local tough guys - the man regularly put up against the corrupt mayor of Stockport. During the current mayoral election the cat's paw dies, and Ezekiel agrees to stand in his place, providing he's guaranteed non-election. He is, of course, elected. A ponderous vehicle, for the naive, exact Lloyd (spouting fortune cookie aphorisms), distinguished only by an extended finale in which Ezekiel rounds up the black hats in a dungeon and forces them to confess their crimes by decapitating two of them (with the help of huge Chinese swordsmen) and parading the corpses, complete with bleeding necks and the heads in bowls on their chests. Sixty years on, political incorrectness, in terms of Oriental stereotypes, doesn't come much more incorrect than this. Una Merkel plays the love interest, Petunia Pratt, with a certain dry irony. [www.timeout.com]